Influence of employee impact on their evaluation of enterprise digital capability: a mediated moderation model - Qiwei Zhou; Lingqiao Zang; Feiqiang Fu (Humanities & Social Sciences Communications)
Abstract Digital transformation elicits new management challenges. Studies have investigated its direct impact on employee behavior, but how employees evaluate enterprise digital capability, and its underlying mechanism remains unknown. Employees’ evaluations of enterprise digital capability tend to shape their subsequent attitudinal and behavioral responses towards the digital transformation, which may ultimately stress influence on the overall transformation initiative in a “bottom-up” manner. Drawing from work design theory and conservation of resources theory, this study proposes that through the implementation of effective work design strategies, organizations can foster a sense of employee impact, and further construes a mediated moderation model regarding how the relationship between employee impact and their evaluation of enterprise digital capability is moderated by empowering leadership, and further, mediated by cognitive adjustment at work. Empirical results based on a three-wave survey featuring 424 full-time Chinese employees show that: employee impact predicts evaluation of enterprise digital capability, and such linkage is not only enhanced by empowering leadership but also strengthened by cognitive adjustment at work. The moderation effect of empowering leadership in the relationship between impact and digital capability evaluation is further mediated by cognitive adjustment at work. We explore the antecedents and mechanisms of differences in employees’ evaluation of enterprise digital capability and propose takeaway managerial messages.